Utilizing a Karaoke App in Learning English Pronunciation: A Case Study of EFL College Students - Hanna Maria Panggabean; Lika Silvia Batubara (International Journal of English and Applied Linguistics (IJEAL), 2022)
The use of karaoke songs as an instrument to learn English pronunciation is considered to be an enjoyable learning method especially to enhance English as Foreign Language (EFL) students' pronunciation skills. In discourse activities, unclear pronunciation might affect the interpretation among peers which might lead to misunderstanding or miscommunication. Because the world is becoming more global, EFL college students as future generations will need to improve their English pronunciation to participate in future international meetings. As Smith (2003) stated, native speakers, tended to be concerned about pronunciation when having conversations with non-native speakers. To minimize misinterpretation, English pronunciation should be given higher attention in listening and speaking instruction. This study surveyed 30 EFL students' experience of learning pronunciation by utilizing a karaoke app, more specifically after listening to an English song and singing via 'Smule-Sing!' karaoke app. This study explained that the listening and singing activities through 'Smule-Sing!' karaoke app assisted EFL learners to produce clear pronunciation devices including word stress, rhythm, intonation, and sounds. However, there are some limitations regarding melody rate and unfamiliarity with the sounds which need to have further research. This study implies the English language and pedagogy to promote and facilitate autonomous learning strategy in EFL students' learning process.